Healthy subjects experience bowel changes on enteral diets: addition of a fiber blend attenuates stool weight and gut bacteria decreases without changes in gas - Koecher, Katie J; Thomas, William; Slavin, Joanne L (JPEN. Journal of parenteral and enteral nutrition, 2015)
Tube-fed patients frequently suffer from abnormal bowel function that affects intestinal bacteria and quality of life. Dietary fiber affects laxation and can be fermented by gut bacteria to metabolites that influence gut health and fecal moisture. The aim of this study was to compare the effects of a fiber-blend fortified enteral formula (FB, 15 g/L), a fiber-free formula (FF), and habitual diet on bowel function, fecal bacteria, and quality of life. In a randomized, double-blind, crossover design, 20 healthy subjects consumed both FF and FB for 14 days with a 4-week washout. A 5-day fecal collection was used to assess stool output, whole-gut transit time (WGTT), total bacteria, bifidobacteria, lactobacilli, clostridia, and bacteroides. Subject gastrointestinal quality of life index (GIQLI) and side effects were also measured. On formula diets, 5-day fecal output decreased by >55% from habitual diet, but was 38% higher on FB than FF (P = .0321). WGTT was approximately 1.5 times longer on formula diets than habitual diet (P < .0004). Total bacteria declined from habitual diet on FF (P < .004), but not on FB. Numbers of bifidobacteria and lactobacilli declined from habitual diet on both formula diets, but bifidobacteria was higher on FB compared with FF (P < .0001). Bacteroides and clostridia numbers did not change between diets. GIQLI and incidence of gas symptoms did not differ between formulas. Addition of a fiber blend moderated changes in bowel function and gut bacteria observed in healthy subjects consuming FF. These results support adding mixed fiber sources to enteral nutrition if no contraindication exists.